2019
DOI: 10.1017/s1355617719000614
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the NIH Toolbox Cognition Battery in Healthy Older Adults: Reliability, Validity, and Agreement with Standard Neuropsychological Tests

Abstract: Objective: Few independent studies have examined the psychometric properties of the NIH Toolbox Cognition Battery (NIHTB-CB) in older adults, despite growing interest its use for clinical purposes. In this paper we report the test-retest reliability and construct validity of the NIHTB-CB, as well as its agreement or concordance with traditional neuropsychological tests of the same construct to determine whether tests could be used interchangeably. Methods: Sixty-one cognitively healthy adults ages 60-80 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 39 publications
5
57
0
Order By: Relevance
“…very short term). A more recent study assessed long-term stability (average 15.03 ± 3.11 months between retest) of NIH-TB uncorrected standardized scores in older adults (Scott et al, 2019), with results indicating a pattern more similar to our investigation. Namely, reliability indices were predominantly moderate in magnitude, though values ranged from 0.46 to 0.87 for individual tests (lower bound of 95% CI range: 0.14-0.77; Scott et al, 2019).…”
Section: Psychological Medicinesupporting
confidence: 83%
See 1 more Smart Citation
“…very short term). A more recent study assessed long-term stability (average 15.03 ± 3.11 months between retest) of NIH-TB uncorrected standardized scores in older adults (Scott et al, 2019), with results indicating a pattern more similar to our investigation. Namely, reliability indices were predominantly moderate in magnitude, though values ranged from 0.46 to 0.87 for individual tests (lower bound of 95% CI range: 0.14-0.77; Scott et al, 2019).…”
Section: Psychological Medicinesupporting
confidence: 83%
“…A more recent study assessed long-term stability (average 15.03 ± 3.11 months between retest) of NIH-TB uncorrected standardized scores in older adults (Scott et al, 2019), with results indicating a pattern more similar to our investigation. Namely, reliability indices were predominantly moderate in magnitude, though values ranged from 0.46 to 0.87 for individual tests (lower bound of 95% CI range: 0.14-0.77; Scott et al, 2019). It is possible that the long retest interval of the present study, as well as that of Scott et al, may have attenuated reliability estimates, and that in agreement with previous literature a shorter retest interval may have yielded better stability estimates.…”
Section: Psychological Medicinesupporting
confidence: 83%
“…Two computerized cognitive assessment batteries that are increasingly being used in clinical research are the Cogstate Brief Battery (CBB; Hammers et al, 2012;Hammers et al, 2011;Maruff et al, 2013) and the NIH Toolbox-Cognition Battery (NIHTB-CB; Heaton et al, 2014;Weintraub et al, 2013). These measures have demonstrated acceptable reliability and construct validity as compared to traditional paper-pencil methods (Casaletto et al, 2015;Heaton et al, 2014) but lack clear support as a replacement for goldstandard neuropsychological assessment (Scott, Sorrell, & Benitez, 2019). Although there has been significant effort put forth to develop representative normative samples for these measures, there continues to be a lack of knowledge around the performance on these two cognitive batteries by individuals from underrepresented populations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, two of the largest studies on the psychometric properties of the CBB make no mention of the race/ethnicity of their samples (Maruff et al, 2013;Mielke et al, 2015), pointing to a lack of information regarding the use of these measures in ethnically diverse populations. With regard to the NIHTB-CB, the original normative data were unadjusted for demographic factors, with subsequent normative samples providing corrections for race/ethnicity (Casaletto et al, 2015); however, it has been found that the NIHTB-CB may overestimate such individuals' deficits (Scott et al, 2019) and more research is needed to validate the clinical utility of this measure. Overall, there remains a fundamental gap in our understanding of the utility of these computerized cognitive batteries for use in clinical research trials including Black adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation